Killer whale range expansion and extended seasonal presence in the eastern Canadian Arctic, 2002-2023 - Steven H. Ferguson; Brooke A. Biddlecombe; Kristin Westdal; Stephen D. Petersen; Cortney Watt; Cory J. D. Matthews; Jeff W. Higdon (Frontiers in Marine Science)
IntroductionThis study examines 20 years of killer whale (Orcinus orca) sightings (2002–2023) in the eastern Canadian Arctic, drawing from a comprehensive sighting database spanning 1850–2023. Despite inherent biases favoring data collection near communities and coastal areas, spatiotemporal analyses reveal significant shifts in killer whale distribution linked to changing sea ice conditions.MethodsWe developed a clustering metric representing the mean distance to the five nearest sightings and included it in a linear model to investigate spatial trends. We investigated temporal trends by modeling the effects of multiple covariates on the ordinal date of killer whale sightings.ResultsSpatial analysis showed that killer whales are progressively moving away from historically high-use areas and that sighting locations are becoming more dispersed over time. A significant year × sea ice interaction in the temporal analyses indicates observations occur earlier during their arrival period at lower sea ice concentrations over time, suggesting that declining sea ice concentration contributes to earlier arrival. Conversely, for departure periods, killer whales are observed farther south later in the year, likely linked to earlier freeze-up at higher latitudes, and are overall observed later into the year over time. This trend has led to a near doubling of their average presence from 26 days in 2002 to 48 days in 2023 (27 July to 13 September) reflecting an extended open-water season.DiscussionThese findings underscore the prolonged seasonal use of Arctic regions by killer whales, driven by diminishing sea ice and expanding open-water habitat. Such shifts highlight potential implications for Arctic marine ecosystems as killer whales increasingly overlap with endemic species.